El Euro: Política monetaria - Varela Parache, Felix (2002)
Since January 1 1999, eleven Europeas countries stated lo juin a coin that is priced in exchange markets: the euro. Also, they have the same monetary policy. Félix Varcla make an analysis of the monetary policy and the exchange rate, considering its evolution, specially in relation to dollar. In the same way, he studies monetary policy as a monetary targeting contrasting with the inflation targeting.